PEMODELAN KAWASAN PASAR SOUVENIR DI DESA TOMOK (Objek Kasus : Desa Wisata Tomok, Kabupaten Samosir, Sumatera Utara) - Sitohang, Ida Nova; Pakpahan, Raimundus; Silitonga, Shanty (Unika Santo Thomas, 2019)
The tourist market or souvenir shop is a place of sale and purchase transactions in tourist areas that sell merchandise typical of the tourist attraction. The tourist market can be classified into the traditional market according to the physical, time, area of activities and goods traded. The tourist market can also be classified as a traditional market according to its function as a culture that is a market that has multiple roles, not only acting as a meeting place between sellers and buyers but the market also has a function as a meeting place for cultures brought by each of them who utilize the market. Trading is one of the economic activities of the Tomok tourism village community to meet the needs of the community. Based on the condition of the souvenir shop building, there are many variations in terms of size, shape and ownership of the shop. One type of merchandise is souvenir as one of the facilities in Tomok village tourist attraction. For this reason the importance of providing the right model in the souvenir market area in the village of Tomok in order to increase the high tourist arrivals of tourist taxis. Simulation and modeling research strategies are a research that using imitation models of a particular process or system that will be examined / tested through a simulation process, both scientific and man-made phenomena. The benefit of this research is to find a model of the souvenir market area in the Tomok tourism village that meets the criteria of market structuring.